LANGUAGE DEVELOPMENT AND SPEECH THERAPY SUPPORT: LITERATURE ANALYSIS - Vindece, Aija; Usca, Svetlana (Education Reform: Education Content Research and Implementation Problems, 2019)
Language disorders, including speech sound disorder, need to be diagnosed at the preschool age as they may jeopardize successful learning and socialization in the long term. Nowadays, there is a growing number of "late talkers", who need to provide speech therapy support at a preschool. The pedagogical tools available do not always meet the needs of today's children.The paper analyzes theoretical insights on the development of language as a complex system, correctional work, and the need to organize a transformative pedagogical and correctional work process that aims at developing the language system and reinforcing articulation of sound, using audiovisual stimulation as a unified system.